A description of an effective process for dealing with complex ethical dilemmas in a tertiary children's hospital. (24th May 2012) - Dave, A; Barrett, T; Rao, S; Watson, J
Abstract : Background: 'A' was referred to the hospital clinical ethics committee; with a rare, genetic, severely life-limiting condition with learning difficulties, endocrine, metabolic and skeletal problems; leading to multi-systemic complications. The key issues were: – To determine the limits of medical treatment in complex cases, involving several professionals. – Dealing with conflict when there was a discrepancy between parental and clinician views – How to determine the best interests of the child. Aims: To discuss analytically, the ethical issues identified in the case of a child presenting with a rare and complex syndrome, with repeated admissions. To disseminate learning around the process used in a tertiary Children's Hospital, of dealing with complex ethical dilemmas. Methods: An analysis of the issues was undertaken, using principles and concepts of medical ethics and law. The process involved detailed, critical and reflective discussions between the referring team and the members of the clinical ethics committee over a continuous period. Parental views as well as 'A's wishes were ascertained using specialist input. Results: The process was felt to be very helpful for all involved with the following benefits and learning points: – It was a good experience to learn to "hear the voice of the mute child" and make 'A' central to decision-making, rather than professional or parental views. – A consensus was achieved on a management plan which felt quite enabling and supportive to the clinical team – It optimised use of clinical and legal resources in the Trust. – It contributed to embed the ethics committee more firmly within the clinical governance arrangements of the hospital contributing towards good quality care. – It helped sustain a fragile therapeutic relationship with the family at a difficult juncture – It potentially helped change practice in a positive way. – Important to involve all the clinical team members rather than the referrer alone. – Flexibility needed in arranging meetings repeatedly and at short notice. Conclusions: There is experiential evidence that referring complex clinical dilemmas to an ethics committee improves clinical effectiveness and patient experience. This needs to be formally evaluated.